Polypyrrole/NiFe2O4 composites with improved hexavalent chromium removal from aqueous solution. Issue 12 (1st December 2015) - Sun, Wanhong; Zhou, Yanqing; Liu, Juanli; Wang, Yanbin; Chen, Lihua; Tian, Ziwen
Abstract : Polypyrrole/NiFe2 O4 (PPy/NiFe2 O4 ) composites were prepared by ultrasonic oxidative polymerization in the presence of NiFe2 O4 nanoparticles (NPs). The nanostructure of PPy/NiFe2 O4 was confirmed by the X‐ray diffraction (XRD), scanning electron microscope (SEM), transmission electron microscope (TEM), and vibrating sample magnetometer (VSM) examinations. The adsorption of Cr(VI) onto the PPy/NiFe2 O4 composite was lowly pH dependent and the adsorption kinetics followed the Pseudo‐second‐order model. The Langmuir isothermal model well described the adsorption isotherm data and the maximum adsorption capacity increased with the increase of temperature. The maximum adsorption capacity of the PPy/NiFe2 O4 for Cr(VI) ions was up to 50 mg/g at pH 2.0. The excellent adsorption characteristic of PPy/NiFe2 O4 composite will render it a highly efficient and economically viable adsorbent for Cr(VI) ions removal. POLYM. COMPOS., 38:2779–2787, 2017. © 2015 Society of Plastics Engineers